Supply chain management best practices, agility, risk management and performance in small and medium enterprises in South Africa - Loury-Okoumba, W. V. (Vaal University of Technology, 2018)
The strategic importance of small and medium enterprises (SMEs) and their role in stimulating economic growth and competitiveness in many countries are well documented in literature. The same applies to South Africa, where the SME sector has grown tremendously to become an important contributor to social and economic development through employment creation and constant input to the gross domestic product. However, in spite of these contributions, South African SMEs face numerous challenges, which negatively impact their prospects for growth and success. Some of these challenges include the limited access to financial capital, the lack of infrastructure and the lack of skills, which play a significant role in the high mortality rate of SMEs. One of the proposed solutions to address these operational challenges is the adoption of supply chain management strategies to strengthen the operational and long-term capabilities of SMEs. Thus, the purpose of this study was to investigate the relationships between supply chain management best practices, supply chain agility, risk management and supply chain performance in South African SMEs. The study applied a quantitative approach in which a cross-sectional survey design was used to collect data to test direct and indirect relationships between different constructs (buyer-supplier collaboration, supply chain integration, total quality management, IT adoption, supply chain agility, supply chain risk management and supply chain performance). A structured survey questionnaire was developed using adapted measurement scales and administered to 407 randomly selected SME owners, managers and professional employees who had some knowledge about supply chain management. The collected quantitative data were analysed using the Statistical Packages for Social Sciences (SPSS version 24.0) and the Analysis of Moment Structures (AMOS version 24.0) statistical software. The actual data analyses techniques applied included descriptive statistics and inferential statistics using structural equation modelling. The latter included a Confirmatory Factor Analysis (CFA) to test the psychometric properties of measurement scales and the testing of the six hypotheses using the path analyses technique. The results of the study showed positive and significant relationships between all supply chain management practices and supply chain agility. Specifically, buyer-supplier collaboration and total quality management exerted a moderate and significant influence on supply chain agility. Moreover, IT adoption had a strong positive and significant relationship with supply chain agility iv while supply chain integration had a weak but significant relationship with the same factor. More results provided from the analysis confirmed the existence of a very strong and significant relationship between supply chain agility and supply chain risk management. In turn, supply chain risk management had a strong positive relationship with supply chain performance. The study also takes note of its contributions to highlight its merits. From a theoretical perspective, it provides an in-depth examination of some driving factors to supply chain agility, supply chain risk management and supply chain performance within SMEs. Given that a study of this nature has not been performed before amongst South African SMEs, the results are an essential addition to the existing body of literature within the area of supply chain management within SMEs in developing countries such as South Africa. From a management perspective, the study suggests that specific attention should be directed to all of the four supply chain management practices (buyer-supplier collaboration, supply chain integration, IT adoption and total quality management) considered as possible avenues to address operational challenges in SMEs.
D. Tech. (Logistics, Faculty of Management Science), Vaal University of Technology
Keywords: Buyer-supplier collaboration, Supply chain integration, IT adoption and Total quality management; Business logistics; Total quality management; Dissertations, Academic -- South Africa